AN OVERVIEW OF ACUTE RESPIRATORY INFECTION CASES BEFORE AND AFTER EXPOSURE TO VOLCANIC ASH - Nienda Mustika Wahyuning Tyas; Rachmah Indawati (Universitas Airlangga, 2019)
Background: Volcanic ash due to volcanic eruptions has an impact on health. Volcanic ash can cause health problems such as irritation and acute respiratory infections (ARI). Purpose: This study aims to know the outlook of ARI cases before and after exposure to volcanic ash. Methods: This research is a descriptive observational study with a cross-sectional approach that used secondary data from Kepohbaru Health Centre. The population of this study was ARI patients in Kepohbaru Health Centre in February 2013 and February 2014. The sampling technique used is total sampling. The analysis used is univariate analysis. Results: The results of this study indicate that before exposure to volcanic ash, the majority of ARI cases were males (52.01%), age group 5–11 years (16.3%), and with no history of ARI (67, 85%). The majority of ARI patients after exposure to volcanic ash were female (53.67%), age group 5–11 years (15.5%), and with no history of ARI (58.37%). More cases of ARI occurred after rather than before exposure to volcanic ash. Conclusion: Before and after exposure, the most common cases of ARI were suffered by respondents in the age group 5–11 years who had no history of respiratory disease. The number of cases of ARI was higher after exposure to volcanic ash. ARI cases happened more on males before exposure, whereas after exposure, it happened more on females.